KAJIAN PERBANDINGAN HISTOLOGI USUS HALUS DAN USUS KASAR ANTARA AYAM HUTAN (Gallaus gallus) DAN AYAM RAS (White leghorn) - Mardhiah, Ainul (Universitas Almuslim, 2015)
This Research aims to determine differences in the small intestine and colon histology coarse chicken (White leghorn) and partridges (Gallus gallus). As a sample of chicken and partridges male, adult weighing 1.75 to 2.00 kg respectively, and 2.00 to 1.2 kg. The amount of each is 2 (two) tail. For histological examination of the small intestine tissue (jejenun) and coarse intestine (cecum) were taken of each of the two (2) different places and fixed with 10% formalin solution, after going through the process of micro-histological techniques, the specimen was cut wear mikrotop with a thickness of 6 (six) microns and stained with Haematoksilin and eosin (HE) histological images obtained using photomikroskop of various magnification. The results showed that the general structure of the small intestine and rough on both types of chicken under study are the same, which is composed of layers of mucosa, submucosa, tunica muscularis and serosa. However, there are differences in specific structures on several network components, especially in the mucosal layer. In the small intestine and rough broiler growth Lieberkuhn glands, mucous mmuskularis grow perfect, but the number of goblet cells less. factors that allow the structural difference is the food, environmental and metabolic activity.Keywords: Chicken Forest, Small intestine and intestine Rough.